Akkermansia muciniphila ameliorates doxorubicin-induced cardiotoxicity by regulating PPARα-dependent mitochondrial biogenesis - Hui Lin; Xian Shao; Haodi Gu; Xinrou Yu; Lingyan He; Jiedong Zhou; Zuoquan Zhong; Shitian Guo; Dan Li; Fei Chen; Yongfei Song; Lili Xu; et al. (npj Biofilms and Microbiomes)
Abstract Doxorubicin (DOX) is a key chemotherapeutic agent but is also a leading cause of DOX-induced cardiotoxicity (DIC), limiting its clinical use. Akkermansia muciniphila (A. muciniphila), known for its benefits as a probiotic in treating metabolic syndrome, has uncertain effects in the context of DIC. Here, 16S rRNA sequencing of fecal samples from anthracycline-treated patients and DIC mice revealed marked depletion of A. muciniphila. Cardiac transcriptomics, supported by in vitro experiments, showed that A. muciniphila colonization improved mitochondrial function and alleviated DIC by activating the PPARα/PGC1α signaling pathway in both normal and antibiotic-treated C57BL/6 mice. Further analysis uncovered a restructured microbiome–metabolome network following A. muciniphila administration, which contributed to DIC protection. Notably, A. muciniphila supplementation increased serum levels of the tryptophan metabolite indole-3-propionic acid (IPA), which binds to the cardiac aryl hydrocarbon receptor (AhR), leading to the activation of the PPARα/PGC1α signaling pathway. In conclusion, our study sheds light on the potential of A. muciniphila as a probiotic in mitigating DIC.